Modification of zero valent iron nanoparticles by sodium alginate and bentonite: Enhanced transport, effective hexavalent chromium removal and reduced bacterial toxicity - Mengya Zhang; Kexin Yi; Xiangwei Zhang; Peng Han; Liu, Wen; Meiping Tong (Journal of Hazardous Materials, 2019)
The rapid aggregation/sedimentation and decreased transport of nanoscale zero-valent iron (nZVI) particles limit their application in groundwater remediation. To decrease the aggregation/sedimentation and increase the transport of nZVI, sodium alginate (a natural polysaccharide) and bentonite (one type of ubiquitous clay) were employed to modify nZVI. Different techniques were utilized to characterize the modified nZVI. We found that modification with either sodium alginate or bentonite could disperse nZVI and shifted their zeta potentials from positive to negative. Comparing with the bare nZVI, the sedimentation rates of modified nZVI either by sodium alginate or bentonite are greatly decreased and their transport are significantly increased. The transport of modified nZVI can be greatly increased by increasing flow rate. Furthermore, Cr(VI) can be efficiently removed by the modified nZVI (both sodium alginate and bentonite modified nZVI). Comparing with bare nZVI, the two types of modified nZVI contain lower toxicities to Escherichia coli. The results of this study indicate that both sodium alginate and bentonite can be employed as potential stabilizers to disperse nZVI and improve their application feasibility for in situ groundwater remediation.
Keywords: Bacterial toxicity; Bentonite; Cr(VI) removal; nZVI modification; Sodium alginate